Syariah, Economic Penerapan Konsep Takaful Sebagai Landasan Operasional Koperasi Syariah ASB: Koperasi Syariah ASB, Mengintegrasikan Prinsip Takaful dalam Model Bisnis - Rosmiati; SH,.MH., Dr. Mahipal; Julianty, Fitri; Robiah, Nabila Salwa; Felix, Florian; Harahap, Abdy Saleh (Jurnal Sains Indonesia, 2025)
This study investigates the application of the takaful concept as the operational foundation of the ASB Islamic Cooperative. Takaful, an Islamic insurance system grounded in mutual assistance and collective fund management through the tabarru’ contract, eschews elements of riba (usury), gharar (uncertainty), and speculation. The integration of takaful into Islamic cooperatives not only provides risk protection for members but also generates returns through Sharia-compliant investment management. This approach aligns with the principles of Islamic cooperatives, which emphasize solidarity and member empowerment, thereby fostering a sense of belonging and ensuring cooperative sustainability. Employing a qualitative methodology, the study conducted interviews at several Islamic cooperatives in West Java Depok, revealing positive responses to takaful integration. The adoption of takaful in Islamic cooperatives is anticipated to bolster their viability by fostering an inclusive and sustainable economic ecosystem. Furthermore, this research seeks to formulate concepts and regulations to support the development of takaful-based Islamic cooperatives, offering a substantive contribution to Sharia-compliant financial management in Indonesia.